A Regularização Fundiária Urbana de Interesse Social (REURB-S) como instrumento de justiça social: o caso da área central da COHAB, em Belém, estado do Pará - Monteiro, Jannice Amóras (2023)
This work had as its proposal the conceptual and normative study regarding the urban land regularization of social interest (REURB-S) as an instrument of social justice, as a legal institute that constitutes an instrument of urban policy in the current Brazilian legal system. Through the analysis of texts, statistical data, electronic pages and monographic works of master's dissertations and doctoral theses, an attempt was made to investigate and understand, above all, the discursive and practical issues that involve urban land regularization as a promoter of social justice, using as a criterion the number of properties that started to be registered in a notary, after going through the process of urban land regularization, analyzing the registration of each of the 107 (one hundred and seven) regularized properties, in order to analyze whether such properties underwent some change in their registrations, transforming or not the regularized property into a financial asset that generates credits in the real estate market, such as, for example, offering them as a credit guarantee for obtaining loans and selling assets themselves, removing them or not from the category of “dead capital”, as defined by Hernando de Soto), choosing the consolidated urban nucleus known as the Central Area of COHAB, in Belém, as the object of the case study, for having object of urban land regularization recently (2021), in Belém. The results attested that the land legitimation practiced was merely titling, with political and/or electoral purposes, and there is, to date, no implementation of public work foreseen in the fixed schedule of works, thus demonstrating how much the REURB practiced in the The Consolidated Urban Core called the Central Area of COHAB is still far from the concepts of the right to the city, the right to decent housing, social justice and SDG 11, which aims to make cities and human settlements inclusive, safe, resilient and sustainable, whose Goal 11.1 deals with guaranteeing access for all to safe, adequate and affordable housing, and to basic services and urbanization of slums. In any case, perhaps it serves as an incentive the verified finding that, in fact, the registration of the land legitimacy of the 107 lots analyzed removed these properties from the classification of “dead capital”, transforming them into a financial asset that can and should be used for benefit the legitimate. It is demonstrated, therefore, that the main objective of urban land regularization, especially that of the social interest modality, must always be full or integral land regularization, with the promotion of social justice, suggesting that both civil society , as inspection bodies such as the Public Prosecutor's Office demand the practice of serious urban land tenure regularizations that ensure the right to the city and to smart and sustainable cities.